The role of hypoxia response element in TGFβ-induced carbonic anhydrase IX expression in Hep3B human hepatoma cells - Yildirim, Hatice; Karaman, Merve; Köçkar, Feray (Archives of Biological Sciences, 2017)
Carbonic anhydrase IX (CAIX) is a hypoxia-regulated gene. It is overexpressed in a variety of cancers, including hepatocellular cancer. Transforming growth factor β (TGFβ) is considered to have an impact on cancer biology dueto its important roles in cell proliferation and differentiation. The effect of the TGFβ on CAIX expression under hypoxia and the mechanism underlying the role of the hypoxia response element (HRE) on this expression areunknown. In this study, we demonstrate that TGFβ upregulates CAIX expression under hypoxic conditions in the Hep3B hepatoma cell line, indicating that the mitogen-activated protein kinase (MAPK)- and phosphatidylinositol-4,5-bisphosphate 3-kinase (PI3K)-signaling pathways might be responsible for this response. Site-directed mutagenesis of the HRE region in CAIX promoter reduced the TGFβ-induced CAIX promoter activity, pointingto the significance of HRE for this response.Upregulation of TGFβ-stimulated CAIX expression was consistent with the upregulation of promoter activity of five different truncated constructs of the CAIX promoter under hypoxia. Our findings show that the HRE region is critical for TGFβ-induced CAIX expression,which is mainly controlled by MAPK and PI3K pathways. https://doi.org/10.2298/ABS161124003Y Received: November 24, 2016; Revised: January 4, 2017; Accepted: January 11, 2017; Published online: January 23, 2017 How to cite this article: Yildirim H, Karaman M, Köçkar F. The role of hypoxia response element in TGFβ-induced carbonic anhydrase IX expression in Hep3B human hepatoma cells. Arch Biol Sci. 2017;69(4):593-601.